Linux & OpenVMS interoperability tricks for old dogs, new dogs, and hot dogs with open systems - Wisniewski, John Robert (Boston, Mass. : Digital, 2003)
Make OpenVMS High Availability systems and low cost Open System computers work together in complex Intranet and Internet environments. Users of Linux, UNIX and the hundreds of thousands of OpenVMS installations world-wide will find invaluable information in Linux and OpenVMS Interoperability. This book gives you access to the best resources of both Linux and OpenVMS systems by providing practical hints, tricks, and step-by-step processes for installing and interoperating both systems. If you've heard one of John Wisniewski's many presentations on the subject, you'll find that he also brings his expertise and his own brand of humor to the task of explaining these operating systems to new and experienced programmers and administrators. Covers the capabilities, features, and advantages of both Linux and OpenVMS Offers tested solutions to practical interoperability problems Provides a basis for you to choose the right operating system for your needs.
Assessing OpenVMS and Linux : the right tool for the right job -- Breaking into OpenVMS and Linux -- TCP/IP for OpenVMS and Linux -- Security tools for OpenVMS and Linux -- X Windows applications : X Windows interoperability with VMS and Linux -- Using e-mail with OpenVMS and Linux -- SMB for Linux and OpenVMS -- Apache VMS and Linux style -- A compendium of open source tools for OpenVMS and Linux.
Includes index.
Keywords: Linux; OpenVMS device drivers; Electronic books